COMPARATIVE STUDY OF VITAMIN B12 DEFICIENCY ASSOCIATED WITH METFORMIN AND METFORMIN IN COMBINATION WITH DPP-4 INHIBITORS IN A TERTIARY CARE HOSPITAL - MISBAH, NABIHA SUBHANI; SIDDIQUA, SYEDA AYESHA; MASOOD, JUWARIA; TADVI, NASER ASHRAF; FATIMA, AROOBA (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: To estimate the prevalence of vitamin B12 deficiency in type 2 diabetes mellitus patients receiving metformin and metformin in combination with DPP-4 inhibitors. To evaluate the vitamin B12 levels induced by long-term metformin usage. Methods: It is a retrospective, comparative study of 6 mo, conducted at Shadan Institute of Medical Sciences, Hyderabad. 300 diabetic patients of age group between 30-85 y of either gender were divided into Group-A, receiving metformin and Group-B, receiving metformin+DPP-4 inhibitors. Ethics committee approval was o btained. The baseline and after 6 mo values of Vitamin B12 were noted and analyzed by using SPSS software. Results: The majority of the patients were from the age group of 56-65 y (n=42, 28%) in Group-A and 46-55 y (n=61, 40.7%) in Group B. Male predominance was observed in both groups (n=81, 54% and n=76, 50.7%). Duration of Diabetes mellitus was ≤5 y in both groups (n=87, 58% and n=112, 74.7%). Vitamin B12 mean values for Group-A (Baseline-478.61, After 6 mo-195.94) and Group-B (Baseline-527.82, After 6 mo-299.05) were obtained. Mean reduction with a statistical significance in both study groups was observed (Group-A-282.66 and Group-B-228.77). Most of the patients showed numbness (14%) in Group-A and general weakness (7.3%) in Group B, respectively. Conclusion: Type 2 diabetic patients who were on metformin therapy only have a prevalence of vitamin B12 deficiency compared to Metformin in combination with DPP-4 inhibitors receiving patients.